Bio-inspired robotics: kinematic and gait analysis of quad and hexa-legged systems - Singh, Spoorthi; Zuber, Mohammad; Bhat, Naman; Kumar.S, Rathina; Basri, Ernnie Illyani; Ahmad, Kamarul Arifin; Yadav, Manish Varun; Hegde, Navya Thirumaleshwar (Universitas Muhammadiyah Yogyakarta, 2025)
Navigating hazardous environments, such as areas with fire risks, wild animal activity, or inaccessible terrains, poses significant challenges, necessitating the development of bio-inspired robotic systems. This study focuses on the biomechanical design and kinematic analysis of a spider-mimicking robot, specifically examining quad and hexa-legged configurations to optimize movement efficiency and stability. The research employed 3D Computer-Aided Design (CAD) in Fusion 360 to model and simulate the robot's leg framework, analyzing deformation, tension, and strain. Fused Deposition Modelling (FDM) with Poly Lactic Acid (PLA) material was used for component fabrication, chosen for its balance of lightweight properties and structural integrity, validated through stress analysis. A single limb’s forward and reverse kinematics were studied, enabling the development of optimized gait patterns. SIMSCAPE Multibody in MATLAB was utilized for dynamic simulations, and Proportional Derivative (PD) and Proportional Integral Derivative (PID) controllers were tested to evaluate trajectory tracking accuracy and stability. Results show that the six-legged configuration exhibits superior stability with a 15% improvement in gait cycle efficiency and a 20% reduction in energy consumption per stride compared to the four-legged counterpart. The use of PID controllers further enhanced performance, achieving a 12% improvement in settling time and reducing oscillations in trajectory tracking tasks. The choice of PLA material ensured durability under operational loads, with minimal deformation over repeated stress cycles. Servomotor selection and configuration were tailored to optimize torque and speed, enabling precise leg control. This study highlights the potential of bio-inspired robots to advance robotic mobility through optimized kinematics and material choices.